Perancangan Sistem Informasi Penggajian Guru pada SMA St. Petrus Medan - Ester Monica Sinaga; Gortap Lumbantoruan; Eviyanti Novita Purba (Majalah Ilmiah METHODA, 2025)
The development of information technology in this case is computer technology to support decision making in modern organizations which enables work in organizations to be completed with information quickly, accurately and efficiently. One very important issue is salary, calculating the required teacher salary data, namely a payroll system that can produce data quickly and accurately. SMA St. Petrus school that still uses manual methods to manage teacher salaries, by recording them in the books, so errors often occur in calculating teacher salaries based on various different details. It is hoped that this payroll information system can create more effective work procedures, especially in treasury and in making reports, and to optimize the results obtained so that teacher payroll information is designed while this system is suitable for use in managing teacher salary data.